Study Performance of the Fiber Bragg Grating as a Dispersion Compensator an Optical Transmission System Using Optisystem Software - Ali Mahdi Hummadi (Journal of Madenat Alelem University College, 2013)
This paper presents the design and simulation of an optical transmission system in optical fiber. Optical fiber is one of the most important communications media in communication system. Due to its versatile advantages and negligible transmission loss it is used in high speed data transmission. Although optical fiber communication has a lot of advantages, dispersion is the main performance limiting factor. There are various types of optical fiber, the Fiber Bragg Grating (FBG) is commonly chosen as important components to compensate the dispersion in optical communication system. Because the low cost of filter for wavelength selection and low insertion loss, it has also customized reflection spectrum and wide bandwidth. The simulation of transmission system will be analyzed based on different parameters by using OptiSystem simulator. By simulating a model of communication system and using the most suitable settings of the system which include input power (dBm), fiber cable length (km) and attenuation coefficient (dB/km) at cable section, there are three different parameters will be investigated, which are Signal power (dBm), Noise power (dBm), output power (Watt), at receiver.